Pemanfaatan Limbah Tongkol Jagung: Produksi dan Pengembangan Usaha Biochar Desa Bangun Sari - Hidayat, Wahyu; Utami, Mia Putri; Nugraha, Muhammad Dimaz; Duryat, Duryat; Febryano, Indra Gumay; Herwanti, Susni; Suri, Intan Fajar (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This community service program aimed to explore the feasibility and benefits of utilizing corn cob waste for biochar production as a sustainable practice that can serve as a solution to address the issues of corn biomass waste, while simultaneously enhancing waste management, improving soil fertility, and stimulating local economic development. Methodology/approach: This community service program involved 27 farmers in Bangun Sari Village, Pesawaran, focusing on biochar benefits for soil improvement. The methodology included technical training on building biochar production facilities from corn biomass using clay kilns, production process training, establishing a biochar production unit, and providing ongoing support for production, packaging, and marketing of biochar. Results/findings: The community service program has significantly improved farmer’s knowledge on the agricultural waste utilization to support sustainable farming in Bangun Sari Village. The community service activity reveals that the application of biochar production technology using clay kiln techniques is easily adoptable by the community and involves relatively low production costs. Conclusion: By focusing on biochar production units, process training, and business development, the program will benefits local farmers and the community. Its success hinges on effective technical implementation and strong community and government support. Continued commitment and collaboration promise long-term positive impacts on environmentally friendly agriculture.